Association between physical activity and scoliosis: a prospective cohort study. (6th December 2018) - Tobias, Jon H; Fairbank, Jeremy; Harding, Ian; Taylor, Hilary J; Clark, Emma M
Abstract: Background: Little is understood about the causes of adolescent onset idiopathic scoliosis (AIS). No prospective studies assessing the association between physical activity and idiopathic adolescent scoliosis have been carried out. We aimed to carry out the first prospective population-based study of this association. Methods: The Avon Longitudinal Study of Parents and Children (ALSPAC) collected self-reported measures of physical ability/activity at ages 18 months and 10 years. Objective measures of physical activity were collected by accelerometry at age 11 years. scoliosis was identified using the dxa scoliosis Method at age 15 years. Participants with scoliosis at age 10 years were excluded. Results: Of 4640 participants at age 15 years who had DXA scans, 267 (5.8%) had scoliosis. At age 18 months, those infants who were able to stand up without being supported were 66% less likely to have developed scoliosis by age 15 ( P  = 0.030) compared with infants who could not. Those children whose mothers reported they did most vigorous physical activity at age 10 years were 53% less likely to develop scoliosis ( P  = 0.027). Those children who did more objectively measured moderate/vigorous physical activity at age 11 were 30% less likely to have developed scoliosis ( P  < 0.001). Results were not affected by adjustment for age, gender, lean mass, fat mass or back pain. Conclusions: We report reduced physical ability and activity as early as age 18 months in those who go on to develop scoliosis by age 15 years. Further research is justified to examine the mechanisms underlying this association.